2015
DOI: 10.3998/ark.5550190.p008.822
|View full text |Cite
|
Sign up to set email alerts
|

Applications of aminocarbazoles in heterocyclic synthesis

Abstract: Aminocarbazoles are versatile building blocks in organic synthesis. This review focuses on the application of aminocarbazoles to generate a large variety of fused carbazole heterocycles such as pyridocarbazoles, isomeric pyridocarbazoles, thiazolocarbazoles, pyrimidocarbazoles, pyrrolocarbazoles, indolocarbazoles, quino-and chromeno-carbazoles and many others. Many of these molecules exhibit promising biological activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Wang et al 21 recently reported the synthesis of 2-(3-(9-ethyl-9H -carbazol-3-yl))ureido)ethyl methacrylate (14), a purple fluorescent monomer, via the nucleophilic addition reaction of 3-amino-9-ethylcarbazole (12) with 2-isocyanatoethyl methacrylate (13) in methylene chloride at room temperature (Scheme 4). The obtained monomer 14 exhibits a broad range of material applications such as functional coatings, optical devices, chemosensors, organic LEDs, and laser active media.…”
Section: Addition Reactions With Isocyanate and Thioamidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al 21 recently reported the synthesis of 2-(3-(9-ethyl-9H -carbazol-3-yl))ureido)ethyl methacrylate (14), a purple fluorescent monomer, via the nucleophilic addition reaction of 3-amino-9-ethylcarbazole (12) with 2-isocyanatoethyl methacrylate (13) in methylene chloride at room temperature (Scheme 4). The obtained monomer 14 exhibits a broad range of material applications such as functional coatings, optical devices, chemosensors, organic LEDs, and laser active media.…”
Section: Addition Reactions With Isocyanate and Thioamidesmentioning
confidence: 99%
“…Among the substituted carbazoles, 3-aminocarbazole plays a significant role in the field of medicinal chemistry, where it is applied as a versatile precursor for the synthesis of several bioactive annulated carbazole derivatives. 14 3-Aminocarbazoles are also considered useful substrates in the synthesis of various dyes and pigments, stabilizers for polymers, pesticides, photographic materials, and diagnostic reagents in cytochemical studies. For instance, 3-amino-9-ethylcarbazole has been widely used as a peroxidase and considered suitable for the colorimetric detection of antibodies in the diagnosis of certain diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Heteroannulated carbazole framework is an important core motif present in a wide range of natural products and pharmaceutically derived drugs . Among them, pyridocarbazoles are an integral part of numerous natural products, bioactive alkaloids, and pharmaceuticals .…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36][37] These reactions provide a rapid synthetic route for assembling polycyclic structures. [38][39][40] As a part of our interest in carbazole heterocycles, 41,42 here we wish to report a new series of polycyclic pyrano [3,2-c]carbazole derivatives by domino Knoevenagelhetero-Diels-Alder reactions.…”
Section: Introductionmentioning
confidence: 99%